2023
DOI: 10.1177/19386400231172248
|View full text |Cite
|
Sign up to set email alerts
|

First Metatarsal Rotation After Scarf Osteotomy for Hallux Valgus

Abstract: Background Recurrence after surgical correction of hallux valgus may be related to coronal rotation of the first metatarsal. The scarf osteotomy is a commonly used procedure for correcting hallux valgus but has limited ability to correct rotation. Using weight-bearing computed tomography (WBCT), we aimed to measure the coronal rotation of the first metatarsal before and after a scarf osteotomy, and correlate these to clinical outcome scores. Methods We retrospectively analyzed 16 feet (15 patients) who had a W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…We were unable to find any studies reporting the relationship between clinical outcomes and sesamoid coverage/pronation in the context of percutaneous hallux valgus surgery. A series of 16 feet by Najefi et al 13 that investigated pronation 12 months following scarf osteotomy found poorer MOXFQ outcome scores in patients with higher postoperative pronation of the metatarsal, which is contradictory to our findings. Ferreira et al 5 evaluated the round sign post-percutaneous hallux valgus surgery in 45 feet and found the proportion of feet with mild or absent pronation increased from 29% to 55%; however, they did not evaluate if this had an impact on clinical PROMs.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We were unable to find any studies reporting the relationship between clinical outcomes and sesamoid coverage/pronation in the context of percutaneous hallux valgus surgery. A series of 16 feet by Najefi et al 13 that investigated pronation 12 months following scarf osteotomy found poorer MOXFQ outcome scores in patients with higher postoperative pronation of the metatarsal, which is contradictory to our findings. Ferreira et al 5 evaluated the round sign post-percutaneous hallux valgus surgery in 45 feet and found the proportion of feet with mild or absent pronation increased from 29% to 55%; however, they did not evaluate if this had an impact on clinical PROMs.…”
Section: Discussioncontrasting
confidence: 99%
“…There are current theories that failure to reduce the sesamoids and residual pronation of the first metatarsal may lead to increased recurrence rates, yet there are very limited studies reporting the clinical outcomes based on sesamoid coverage or residual pronation. 2 , 4 , 13 , 14 , 20 Chen et al 2 found correcting the tibial sesamoid position to less than grade IV (using the Hardy and Clapham classification) led to poorer functional outcome and patient satisfaction 2 years following surgery in a large series of 250 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations